2008
DOI: 10.1080/09637480701417566
|View full text |Cite
|
Sign up to set email alerts
|

Extractability of selected mineral and trace elements in infusions of chamomile

Abstract: Chamomile flower heads were extracted with boiling water and the elements calcium, potassium, magnesium, zinc and cadmium were recorded in the drug and the resulting infusions. The extractabilities for calcium, magnesium and potassium in the infusions were 19-23%, 47-48% and 65-73%, respectively. Cadmium could be recovered to 15-21% in the infusions and zinc to 23-34%. A longer extraction time gave slightly higher recovery rates for potassium and zinc. The extraction of less plant material gave a slight reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
1
8
0
1
Order By: Relevance
“…For a light water reactor (as the Budapest Research Reactor), using the mean of five values delivered by this reference 32.8 mg of P in the sample gives the same 28 Al activity as 0.01 mg of Al. Picking up the corresponding phosphorus content of our plants from [3846] can calculate the mean P concentrations (mg/kg), as follows: coriander 4041, dill 1745, Echinacea 2810, lavender 2810, chamomile 3635, mint 4046, plantain 4790, and Tobacco 4630 (from IPE 205) [20]. From these data, the following correction rates can be calculated for each of the plants: 4.07%, 0.34%, 1.80%, 0.01%, 0.33%, 0.13%, 0.06%, and 0.25%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a light water reactor (as the Budapest Research Reactor), using the mean of five values delivered by this reference 32.8 mg of P in the sample gives the same 28 Al activity as 0.01 mg of Al. Picking up the corresponding phosphorus content of our plants from [3846] can calculate the mean P concentrations (mg/kg), as follows: coriander 4041, dill 1745, Echinacea 2810, lavender 2810, chamomile 3635, mint 4046, plantain 4790, and Tobacco 4630 (from IPE 205) [20]. From these data, the following correction rates can be calculated for each of the plants: 4.07%, 0.34%, 1.80%, 0.01%, 0.33%, 0.13%, 0.06%, and 0.25%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the papers mentioned at the analysis of Figure 2(a), for comparison reasons concerning the metals represented in Figure 2(b), the following references were used: [38, 78–81]. …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the essential and trace elements in food and medicinal plants have been studied by several research groups worldwide (i.e. Chizzola et al, 2008;Del Vitto et al, 2009;Kara, 2009;Martins et al, 2009;Nookabkaew et al, 2006). Moreover, determining the level of minerals can contribute both to an effective quality control and traceability of herbal medicines, and even to establish the safety of its use in terms of levels of toxic elements.…”
Section: Introductionmentioning
confidence: 99%
“…In general, aromatic plants cannot be considered as phytoextractors, not only because most of the accumulated heavy metals are stored in their roots, but also because their biomass is low. These results clearly exclude aromatic plants grown on heavy metal contaminated fields (at least the plants we examined), from either phytoremediation processes, or from consumption as food supplements or herbs, or for herbal teas, as some of their heavy metal content is expected to be extracted to the concoction (Schilcher and Peters 1990;Chizzola et al 2008;Arpadjan et al 2008;Affholder et al 2013). However, careful analysis of the extracted essential oils from plants grown at all the conditions tested showed that neither the quality and the content of the oils were altered significantly, nor detectable amounts of heavy metals were found in these oils.…”
Section: Discussionmentioning
confidence: 99%